2017
DOI: 10.1002/celc.201600731
|View full text |Cite
|
Sign up to set email alerts
|

Correlation between CO Oxidation and H Adsorption/Desorption on Pt Surfaces in a Wide pH Range: The Role of Alkali Cations

Abstract: It is well‐known that hydrogen adsorption/desorption on Pt open surfaces sites (110 and 100) shows a dependence on the pH below a pure Nernstian shift. Also, it is recognized that the oxidation of CO (and organic molecules) on Pt open surface electrodes occurs at more negative potentials in alkaline media than in acidic solutions. In contrast, both electrochemical processes develop a pure Nernstian behavior at the close‐packed Pt(111) over the whole pH range. The current work employs experimental results of hy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 24 publications
0
13
0
Order By: Relevance
“…Furthermore, anions and cations play an important role in electrocatalysis at low and high pH, respectively . Sulfate and phosphate species adsorb stronger on Pt surfaces than perchlorate species and therefore higher catalytic activity toward the EOR in perchloric acid solution is observed.…”
Section: Single‐crystal Studiesmentioning
confidence: 99%
See 3 more Smart Citations
“…Furthermore, anions and cations play an important role in electrocatalysis at low and high pH, respectively . Sulfate and phosphate species adsorb stronger on Pt surfaces than perchlorate species and therefore higher catalytic activity toward the EOR in perchloric acid solution is observed.…”
Section: Single‐crystal Studiesmentioning
confidence: 99%
“…Sulfate and phosphate species adsorb stronger on Pt surfaces than perchlorate species and therefore higher catalytic activity toward the EOR in perchloric acid solution is observed. On the other hand, at high pH metal cation species change the adsorption potential of hydroxide species at open surface, which are necessary to oxidize and remove the main catalyst poison (CO) from the catalyst surface . The role of alkali cations (Li + , Na + , K + , Cs + , and Be 2+ ) on the oxidative stripping of carbon monoxide from stepped Pt single‐crystal electrodes in alkaline media has been reported .…”
Section: Single‐crystal Studiesmentioning
confidence: 99%
See 2 more Smart Citations
“…Interestingly, Pt/rGO-TT and Pt/C develops inflection points at short times at the same potential range (0.65 ≤ E ≤ 0.75), where the onset potential for the CO removal ( Figure 5) and the pre-peak at the potentiodynamic experiments in presence of methanol is observed ( Figure 6). This result suggests a change of rate-determining step (RDS), which may be attributed to an enhancement of the water dissociation reaction (i.e., OH ad formation) necessary to remove CO from the catalyst surface [34,35]. Additionally, it is observed that at E ≥ 0.85 V (anodic peak during the positive sweep potential, Figure 6), the current decay is faster at Pt/rGO-TT and Pt/C, which is related to the low performance of Pt oxide surface toward the MOR [36].…”
Section: Electrochemical Characterizationmentioning
confidence: 99%